Time to develop severe acute malnutrition and its predictors among children living with HIV in the era of test and treat strategies at South Gondar hospitals, northwest, Ethiopia, 2021: a multicentre retrospective cohort study - Ermias Sisay Chanie; Getasew Legas; Shimeles Biru Zewude; Maru Mekie; Dagne Addisu Sewyew; Enyew Dagnew Yehuala; Abenezer Melkie; Minale Bezie Ambie; Mengesha Assefa; Fitalew Tadele Admasu; Getachew Yideg Yitbarek; Sintayehu Asnakew; et al. (BMC, 2022)
Abstract Background Although severe acute malnutrition is a major public issue among HIV infected children, there is no prior evidence in Ethiopia. Hence, this study aims to assess the time to develop severe acute malnutrition and its predictors among children living with human immunodeficiency virus in Ethiopia, 2012. Methods An institution based retrospective cohort study was conducted in South Gondar hospitals among 363 HIV infected children from February 10, 2014, to January 7, 2021. Epi-data version 3.1 was used to enter data, which was then exported to STATA version 14 for analysis. Besides, WHO (World Health Organization) Anthro Plus software was used to assess the nutritional status of the children. A standardized data extraction tool was used to collect the data. The Kaplan Meier survival curve was used to estimate the median survival time. The Cox-proportional hazard model assumption was checked via the Schoenfeld residual ph test and a stph plot. Bivariable and multivariable Cox proportional hazard models were employed at 95% confidence intervals (CI). A variable having a p-value < 0.05 was considered a statistically significant predictor of severe acute malnutrition. Results A total of 363 children living with HIV, 97 (26.72%) developed severe acute malnutrition during the follow-up period. The overall incidence rate was 5.4 (95% CI: 4.7-5.9) person per year with a total of 21, 492 months or 1791 years of observation. Moreover, the median survival time was 126 months. Treatment failure [AHR =3.4 (95% CI: 2.05-5.75)], CD4 count below threshold [AHR =2.5 (95% CI: 1.64-3.95)], and WHO stage III & IV [AHR =2.9 (95% CI: 1.74-4.73)] were all significant predictors of severe acute malnutrition. Conclusion The time to develop severe acute malnutrition was found to be very low. Treatment failure, CD4 count below threshold, and WHO stage III were all significant predictors of severe acute malnutrition. Hence, emphasizing those predictor variables is essential for preventing and controlling the occurrence of severe acute malnutrition among HIV infected children.